2019
DOI: 10.1111/dmcn.14448
|View full text |Cite
|
Sign up to set email alerts
|

Visuoperceptual profiles of children using the Flemish cerebral visual impairment questionnaire

Abstract: Aim To investigate the underlying factor structure of the 46‐item Flemish cerebral visual impairment (CVI) questionnaire, differentiate the factor scores of children with and without CVI, and examine the impact of comorbidities on factor scores. Method The records of 630 children (386 males, 244 females; median age 77mo; interquartile range 63–98mo) who visited the CVI clinic and the Centre for Developmental Disabilities at the University Hospitals of Leuven from 2001 to 2018 were reviewed systematically. Incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 38 publications
2
46
1
Order By: Relevance
“…Neuroimaging was reported in 29 (63.0%) articles. The most commonly reported imaging technique was MRI ( n = 22) 20,21,28–34,41,44,45,47,48,50,51,56–58,64–66 . Ten articles reported use of CT scans 20,21,29–31,35,46,51,58,65 and five reported use of ultrasound 29,31,45,48,51 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Neuroimaging was reported in 29 (63.0%) articles. The most commonly reported imaging technique was MRI ( n = 22) 20,21,28–34,41,44,45,47,48,50,51,56–58,64–66 . Ten articles reported use of CT scans 20,21,29–31,35,46,51,58,65 and five reported use of ultrasound 29,31,45,48,51 .…”
Section: Resultsmentioning
confidence: 99%
“…In her book, she uses a 25‐item questionnaire which parents complete during a face‐to‐face interview with the clinician 72 . Two articles included in the present review reported use of the Flemish CVI questionnaire developed by Ortibus and colleagues 50,66 . This questionnaire was designed as a screening tool to seek evidence of behaviours associated with CVI and contains 46 items 50 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations